Bridging conceptual understanding and mathematical representation through game-based cuboid learning in junior high school - Latifa, Ulfa; Indrasari, Peti; Pramuditya, Surya Amami; Asnawati, Sri (Jurnal Elemen, 2025)
In the era of modernisation, conceptual understanding and mathematical representation are key components of education. However, many students still encounter difficulties in understanding and accurately representing rectangular prisms. This study addresses the need for innovative learning by examining students' experiences in understanding and representing rectangular prisms through a Role-Playing Game-based educational game and module. This study employed a qualitative method to understand the experiences of 17 eighth-grade junior high school students in learning rectangular prisms through an RPG game and a supplementary module. Data were collected through observation, module analysis, and documentation and then analysed thematically. The findings revealed that while some students found it easier to grasp concepts through visual exploration, others struggled to apply these concepts flexibly beyond the game. Students who actively engaged in gameplay demonstrated a deeper understanding and were better able to make meaningful conceptual connections. Although verbal representation improved significantly, symbolic representation remained challenging for some students. This study emphasises the importance of designing educational games that support conceptual understanding and representation skills. The implications of this study highlight the need for the development of interactive learning media that can facilitate students' conceptual connections and foster their mathematical representation skills.